2016
DOI: 10.1007/s40145-016-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface morphology on wettability conversion

Abstract: Abstract:A hierarchical structural surface of TiO 2 film with reversibly light-switchable wettability between superhydrophobicity and superhydrophilicity on metal substrate was fabricated through simply dip-coating method from TiO 2 precursor solution containing TiO 2 nanoparticles with the average diameter 25 nm (P25), followed by heat-treatment and modification with fluoroalkylsilane (FAS) molecules. The morphology, phase and crystallographic structure, and chemical composite of the as-prepared TiO 2 film we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…As can be seen, with the increase of 5‐AVA concentration, the contact angle gradually increases, and the wettability of the substrate decreases slightly, which is related to the decrease of hydrophilic hydroxyl groups on the surface of ITO. [ 34 ] However, the slight decrease in wettability did not affect the precursor coating obviously, as all perovskite films exhibited compact and uniform full coverage with almost the same grain size shown in Figure 3f–j. From the SEM images we observed that the perovskite film deposited on the ITO/5‐AVA has slightly larger grains than pristine, which may be attributed to the decrease of nucleation density due to the slightly worse wettability and the preferential growth of perovskite induced by 5‐AVA.…”
Section: Resultsmentioning
confidence: 98%
“…As can be seen, with the increase of 5‐AVA concentration, the contact angle gradually increases, and the wettability of the substrate decreases slightly, which is related to the decrease of hydrophilic hydroxyl groups on the surface of ITO. [ 34 ] However, the slight decrease in wettability did not affect the precursor coating obviously, as all perovskite films exhibited compact and uniform full coverage with almost the same grain size shown in Figure 3f–j. From the SEM images we observed that the perovskite film deposited on the ITO/5‐AVA has slightly larger grains than pristine, which may be attributed to the decrease of nucleation density due to the slightly worse wettability and the preferential growth of perovskite induced by 5‐AVA.…”
Section: Resultsmentioning
confidence: 98%
“…However, the obtained results confirm that the presence of TiO 2 layers on the surface of coated glass, after being irradiated by UV light, did not have a significant effect on decreasing the CA value. It is due to the presence of oxygen atoms from OTS molecules can gradually replace the oxygen vacancies on TiO 2 film to maintain the hydrophobicity [21].…”
Section: Mechanical and Chemical Stabilitymentioning
confidence: 99%
“…There are several studies that have been reported on developing superhydrophobic coating through this combination method. Kong et al have prepared superhydrophobic coating on glass substrate by fabricated a micro-/nanostructured TiO 2 film via the sol-gel dip-coating method and then modified by fluoroalkylsilane molecules [18]. The asprepared coatings not only showed a high static water CA up to 165.6°but also enhanced the reversible wettability conversion between hydrophobicity and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those parameters indeed control the final void content and interfacial properties of the composite parts. Fibre surface chemistry and morphology affect wetting properties [1]. Therefore, the surface properties of fibres affect their impregnation during manufacturing and thus directly the quality of the fibre / matrix adhesion.…”
Section: Introductionmentioning
confidence: 99%